2020
DOI: 10.1126/sciadv.aax8847
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps exacerbate neurological deficits after traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a major cause of mortality and morbidity. Preventative measures reduce injury incidence and/or severity, yet one-third of hospitalized patients with TBI die from secondary pathological processes that develop during supervised care. Neutrophils, which orchestrate innate immune responses, worsen TBI outcomes via undefined mechanisms. We hypothesized that formation of neutrophil extracellular traps (NETs), a purported mechanism of microbial trapping, exacerbates acute neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 43 publications
(49 reference statements)
12
131
0
Order By: Relevance
“…Once inside the brain, peripheral immune cells secrete large amounts of inflammatory mediators, which add to further tissue damage and remodeling [ 200 , 201 , 202 , 203 ]. Many studies have reported upregulated expression of IL-1β, TNF-α, IL-6, CCL2, CCL3, CXCL1, CXCL2, CXCL8/IL-8, CXCL10, CCR2, CCR5, CXCR4, and CX3CR1 within 6 h of TBI [ 204 , 205 , 206 ]. Similar to animal models of TBI, the levels of many cytokines and chemokines peak at 4 h post-injury in patients [ 207 , 208 ].…”
Section: Inflammationmentioning
confidence: 99%
“…Once inside the brain, peripheral immune cells secrete large amounts of inflammatory mediators, which add to further tissue damage and remodeling [ 200 , 201 , 202 , 203 ]. Many studies have reported upregulated expression of IL-1β, TNF-α, IL-6, CCL2, CCL3, CXCL1, CXCL2, CXCL8/IL-8, CXCL10, CCR2, CCR5, CXCR4, and CX3CR1 within 6 h of TBI [ 204 , 205 , 206 ]. Similar to animal models of TBI, the levels of many cytokines and chemokines peak at 4 h post-injury in patients [ 207 , 208 ].…”
Section: Inflammationmentioning
confidence: 99%
“…There are no current NET formation reports in the injured spinal cord; however, it has been reported that infiltrated neutrophils in CNS release NETs, which may contribute to the blood-brain barrier damage and neural injury in some CNS disorders such as neurodegeneration, multiple sclerosis, traumatic brain injury (TBI), and ischemic stroke (Tillack et al, 2013;Perez-de-Puig et al, 2015;Laridan et al, 2017;Pietronigro et al, 2017;Valles et al, 2017;Ducroux et al, 2018;Farkas et al, 2019;Novotny et al, 2020;Vaibhav et al, 2020). Vaibhav et al (2020) reported recently that NET formation worsens TBI outcomes, which is regulated by TLR4 and downstream kinase peptidylarginine deiminase 4 (PAD4). Importantly, therapeutically targeting NETs by administration of recombinant human DNase-I degrades NETs and improves neurological outcomes (Vaibhav et al, 2020).…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…Indeed, impaired degradation of NETs is clinically associated with acute thrombotic microangiopathies [ 140 ], while the presence of citrullinated histone H3, a biomarker of NET formation, within thrombi retrieved from acute ischemic stroke patients was independently associated with patient mortality [ 141 , 142 ]. Of interest, we recently reported that elevated NET formation was associated with microvascular occlusion and cerebral hypoperfusion after acute brain injury in both mice and humans [ 143 ]. Conversely, administration of recombinant human DNase-I, an FDA-approved drug under investigation for the management of COVID-19-induced ARDS [ 144 ], improved blood flow and outcomes after both experimental stroke and traumatic brain injury [ 143 , 145 147 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, we recently reported that elevated NET formation was associated with microvascular occlusion and cerebral hypoperfusion after acute brain injury in both mice and humans [ 143 ]. Conversely, administration of recombinant human DNase-I, an FDA-approved drug under investigation for the management of COVID-19-induced ARDS [ 144 ], improved blood flow and outcomes after both experimental stroke and traumatic brain injury [ 143 , 145 147 ]. Thus, the widespread generation of NETs after SARS-CoV-2 may provide a potential target to reduce acute and chronic neurological consequences, including headache, elevated stroke risk, and potential cognitive issues due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%